อัลกอริทึมสำหรับตรวจจับเม็ดตะกั่วบนหัวอ่านเขียนฮาร์ดดิสก์ - Fuangpian, Thanapoom; Muneesawang, Paisarn; Yammen, Suchaart (Asian Health, Science and Technology Reports, 2011)
ปัจจุบันนี้การตรวจจับจุดบกพร่องบนพื้นผิวฮาร์ดดิสก์ไดร์ฟได้นำการประมวลผลภาพแบบดิจิตอลนำมาประยุกต์ใช้สำหรับตรวจจับแทน การตรวจจับด้วยสายตาของมนุษย์ งานวิจัยนี้นำเสนออัลกอริทึมสำหรับตรวจจับเม็ดตะกั่วบนหัวอ่านเขียนฮาร์ดดิสก์อัตโนมัติ ทั้ง 2 กรณี คือ เม็ดตะกั่วบนหัวอ่านเขียนฮาร์ดดิสก์หายไปและเม็ดตะกั่วบนหัวอ่านเขียนฮาร์ดดิสก์ไหม้ ซึ่งทำการทดลองทั้งหมด 3 วิธี ดังนี้ วิธีการจัดกลุ่มด้วยเทคนิคเคมีน วิธีค่าขีดแบ่งที่เหมาะสมด้วยโอซึและวิธีคุณลักษณะเดน่ ดว้ ยรปู เรขาคณิต ขนั้ ตอนแรกทำการเลือกบริเวณทสี่ นใจและตัดภาพย่อยเฉพาะบริเวณเม็ดตะกั่วจากภาพสีหัวอ่านเขียนฮาร์ดดิสก์ ต่อมาวิธีการจัดกลุ่มด้วยเทคนิคเคมีนประมวลผลด้วยภาพย่อยที่เป็นภาพสีถัดมาวิธีค่าขีดแบ่งที่เหมาะสมด้วยโอซึประมวลผลด้วยภาพย่อยที่เป็นภาพระดับเทาที่ได้มาจากการปรับปรุงภาพย่อยที่เป็นภาพสี หลังจากนั้นวิธีคุณลักษณะเด่นด้วยรูปเรขาคณิตประมวลผลด้วยภาพย่อยขาวดำที่ได้มาจากการปรับปรุงภาพย่อยที่เป็นภาพสี สุดท้ายนำภาพย่อยที่ผ่านกระบวนการทั้ง 3 วิธีดังกล่าวแล้วทำการทรานสโพสและรวมด้วยวิธีเมตริกซ์เพื่อบ่งบอกจุดบกพร่องเม็ดตะกั่วบนหัวอ่านเขียนฮาร์ดดิสก์ จากผลงานวิจัยนี้ทดลองกับภาพหัวอ่านเขียนฮาร์ดดิสก์ทั้งหมด 591 ภาพตัวอย่าง พบว่าวิธีการจัดกลุ่มด้วยเทคนิคเคมีนเหมาะสมกับการตรวจจับเม็ดตะกั่วบนหัวอ่านเขียนฮาร์ดดิสก์หายไปและเม็ดตะกั่วบนหัวอ่านเขียนฮาร์ดดิสก์ไหม้มากที่สุด At present, the digital image processing has been applied for defect detection on the surface of a hard disk drive in stead of visual detection. This study is presented how to use an algorithm for detection of solder balls on head gimbals assembly (HGA) automatically in both cases: the missing solder balls on HGA and the solder balls burning on HGA. The experiment is all done in 3 methods: the method of clustering by K-mean technique, the method of appropriately thresholding by Otsu, and the method of geometric feature extraction. The first method is done by choosing the interesting area and cropping only the part around the solder balls from HGA color image. Then the second method, the method of clustering by K-mean, is processed with the cropped color image. Next, the appropriately thresholding by Otsu processes the cropped gray image which is derived from the cropped color image improved. After that, the geometric feature extraction processes the cropped binary image derived from the cropped color image improved. Finally, the processed images from 3 methods above are transposed and combined by matrix method to indicate the solder balls on HGA. The results of this study tested with all 591 HGA sample images are found that the method of grouping by K-mean is the most appropriate method to detect missing solder balls on HGA and solder balls burning on HGA.